Streptozotocin: Pharmacology, effectiveness and side effects - Samuel, Renata O.; Azuma, Mariane M. [UNESP]; Sumida, Dóris H. [UNESP]; Sivieri-Araújo, Gustavo [UNESP]; Jacinto, Rogério de C. [UNESP]; Dezan-Júnior, Eloi [UNESP]; Gomes-Filho, João E. [UNESP]; Cintra, Luciano T.A. [UNESP] (My University, 2018)
Streptozotocin (STZ) is a compound that was originally identified in the late 1950s as an antibiotic, and currently is widely used to induce experimental diabetes mellitus. Its mechanism of action is because STZ enters Beta-cells (β-cells) via the GLUT2 transporter and accumulates intracellularly, being a glucose analogue. Although STZ has been used in research, there is no standardization of a well-established protocol. It's important to highlight that STZ has non-specific toxicity on other organs elicited, which can contribute to variability in its outcomes. In addition, the variability may occur due to the wide range of protocols, including the association of STZ with nicotinamide or hypercaloric diets, variations in the dosage route, drug concentration, lineage and gender of the animal model. Thus, it is necessary to consider the relationship between the induction methodology and the possible pharmacological interactions, evaluating its advantages and disadvantages. This review aims to relate the influence of different protocols of induction of diabetes mellitus with STZ on the effectiveness of the method and possible side effects of this compound.
Keywords: Animal model; Diabetes mellitus; Streptozotocin